Seven-year follow-up of a patient with hereditary gingival fibromatosis treated with a multidisciplinary approach: case report - Ning Li; Wenfang Wang; Yuanyuan Sun; Hongning Wang; Tiejun Wang (BMC, 2021)
Abstract Background Hereditary gingival fibromatosis (HGF) is rare in clinical practice, and the long-term results of the combined orthodontic-periodontal treatment of HGF are rarely reported. Case presentation This study reports for the first time the results of seven years of follow-up in a seven-year-old girl with HGF. The diagnosis was confirmed by clinical signs, family history and histopathological examination. First, periodontal scaling and oral hygiene reinforcement were performed regularly in the mixed dentition stage. Next, gingivoplasty was performed on the permanent dentition. Two months after the surgery, treatment with fixed orthodontic appliances was conducted. The teeth were polished on a monthly basis, and oral hygiene was reinforced to control gingival enlargement. Gingival hypertrophy recurred slightly, and gingivectomies were performed in the months following the start of orthodontic treatment. Follow-up was performed for 24 months with orthodontic retention, and gingival enlargement remained stable after the combined treatment. Conclusions The risk of gingival hyperplasia recurrence during and after orthodontic treatment is high, but satisfying long-term outcomes can be achieved with gingivectomy, malocclusion correction, and regular follow-up maintenance.